Small animal dental equipment, materials, and techniques - Bellows, Jan (John Wiley & Sons, Inc., 2019)
Animal Dental Equipment, Materials, and Techniques: A Primer invaluable. The author has gone back to basics to fill in the gap between limited and advanced veterinary dental services. This book will show you how to establish an efficient dental operatory and perform many of the day-to-day techniques required to raise your level of dental services. The goal of this book is to educate veterinarians and veterinary technicians on the philosophy and means of integrating dental health practices into the everyday life of their patients. The author also explains how to choose dental equipment and materials as well as how to perform basic and intermediate dental procedures based on examination finding. Coverage includes the materials, equipment, and techniques that veterinarians have found most valuable in the practice of veterinary dentistry.--Provided by publisher.